Promoting Cyber Ethics Compliance among Teachers in Tanzania: What should be done? - Hamisi Mfaume; Margareth Bilinga (Journal of Learning for Development)
The invention of digital ICT devices is one of the most important developments in the history of humankind, and education can greatly benefit from it. However, cyber ethics violations by teachers have become prevalent and are expected to increase unless measures are taken. This study explored education stakeholders’ perspectives on ways to promote teachers’ compliance with cyber ethics in Tanzania. It employed a qualitative case study design involving three secondary schools and 27 participants selected purposively in Kinondoni Municipality in the Dar es Salaam region. Data were sought through semi-structured interviews and document reviews and subjected to thematic data analysis. The findings indicated that teachers’ compliance with cyber ethics requires training of teachers on the pedagogical uses of technology, the inception of a specific national policy for the responsible use of technology in schools, integration of the cyber ethics aspects of the Teachers’ Code of Conduct, improvement of teachers’ living and working conditions, and promotion of teachers’ awareness of the Cyber Crimes Act of 2015, among others. The study recommends that policymakers and education authorities implement the suggested initiatives to promote cyber ethics compliance among teachers for education excellence in Tanzania, and, possibly, elsewhere.